Pathogenic Potential of Composted and Sundried Human Excreta from Eco-toilets in Bangladesh (Journal of Monno Medical College, 2023)
Background: The concept of eco-toilets in Bangladesh was promoted by an NGO (Practical Action, Bangladesh). The ecotoilets are especially built to collect human excreta for using them as manure on the fields after appropriate treatment for 12 months.Objectives: This study was designed to see the physical properties appropriate for fields and pathogenic potential to ensure the treated human excreta are safe for cultivator’s handling.Methodology: The study was carried out in three phases during 2010 to 2014. A total of 210 composted faecal excreta were examined for physical properties like colour, odour, odour intensity, moisture, bacteriological examination for faecally transmitted potential bacteria and parasitological examination for ova / cysts of faecally - transmitted parasites to recommend whether these composted excreta were suitable for use as manure by the cultivators.Results: Majority of the specimens in all three phases contained remarkable moisture: 22.3-80.0% in all specimens in phase I, a considerable number (16, 53.3%) contained 25% moisture in phase II and high moisture content (66.4%-78.9%) in 6(50.0%) of specimens in phase III. Bacteriological examination revealed no pathogenic organism in any specimen of the phases- although, some specimens in all phases showed growth of non-coliform bacteria. Parasitological examinations in all phases revealed ova/larvae of helminths of Ascaris lumbricoides (AL)/ Trichuris trichiura (TT)/ Strongyloides stercoralis (SS). No cyst or trophozoite of any pathogenic parasite, or oocyst of the cryptosporidium was found.Conclusion: The composted excreta could not be adequately treated by sun-drying as indicated by high moisture content and were found not suitable to use as manure by cultivators in the field.J Monno Med Coll June 2022;8(2): 44-47